Ambulatory Oxygen for Pulmonary Fibrosis (OxyPuF): a randomised controlled trial and acceptability study - Rachel L Adams; Alisha Maher; Nicola Gale; Anjali Crawshaw; David Thickett; Alice M Turner (Health Technology Assessment)
Introduction Idiopathic pulmonary fibrosis is a devastating condition of unknown cause that results in progressive, irreversible scarring of the lung, manifesting as breathlessness and dry cough. Idiopathic pulmonary fibrosis is thought to be responsible for as many as 1 in 100 deaths in the United Kingdom, killing 5300 people a year. Ambulatory oxygen therapy is commonly used in idiopathic pulmonary fibrosis to relieve exertional breathlessness, although evidence to support this strategy is lacking. This pragmatic randomised controlled trial was planned to test whether use of ambulatory oxygen therapy is beneficial in people with idiopathic pulmonary fibrosis. Methods We planned a randomised controlled trial in 260 patients with idiopathic pulmonary fibrosis who are breathless on exertion and do not meet criteria for long-term oxygen therapy, randomising in a 1 : 1 ratio between ambulatory oxygen therapy and best supportive care. Primary outcome was a quality-of-life questionnaire validated in pulmonary fibrosis, the King’s Brief Interstitial Lung Disease questionnaire, measured at 6 months. We calculated our sample size based on the minimum clinically important difference of four units and standard deviation equal to 8.85 in King’s Brief Interstitial Lung Disease questionnaire; assuming power of 90% and 5% two-sided significance level, thus required 130 per arm, after accounting for 20% dropout. The trials unit’s web-based randomisation algorithm minimises on factors potentially influencing response to ambulatory oxygen therapy, such as severity of idiopathic pulmonary fibrosis, desaturation to < 88% present on walking, current or recent (within 6 months) pulmonary rehabilitation, and recruitment centre. Secondary outcomes included symptoms, exercise capacity and cost-effectiveness. A process evaluation included assessment of trial fidelity and acceptability of the intervention with use of qualitative research methods and arts approaches with patients and staff. Qualitative interviews were conducted with patients from the Ambulatory Oxygen for Pulmonary Fibrosis trial and the idiopathic pulmonary fibrosis patient support group Action for Pulmonary Fibrosis, and stakeholders: healthcare professionals and policy-makers. Interviews were audio-recorded, transcribed clean verbatim. Photovoice methodology was conducted with patients. A workshop prior to data collection informed and guided data collection and analysis. Traditional qualitative analysis and arts-based coproduction analysis approaches were used to produce a short film. An economic model was planned but could not occur due to early termination. Results The trial was stopped prematurely due to low recruitment. This was due to a combination of the impact of COVID-19 on research infrastructure, financial issues for sites with the payment structure for the trial and lack of equipoise which limited site recruitment. Seven out of 25 eligible, interested patients were randomised after pre-screening, implying a lack of interest among patients in the study. Baseline characteristics indicated that patients were elderly (mean age 81) and predominantly male. Qualitative work with 11 patients and 23 other stakeholders concluded that ambulatory oxygen therapy is desirable, acceptable and widely commissioned in the United Kingdom, such that further trials are not likely to be feasible. Conclusion Although we are not able to formally address our objectives of assessing efficacy and cost-effectiveness of ambulatory oxygen therapy in idiopathic pulmonary fibrosis, it is unlikely that conducting a randomised controlled trial is feasible due to lack of equipoise. Funding This synopsis presents independent research funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme as award number NIHR131149. Plain language summary Idiopathic pulmonary fibrosis is responsible for as many as 1 in 100 deaths in the UK, killing 5300 people a year. Initially, sufferers notice shortness of breath and a persistent dry cough. As a result of breathlessness, patients reduce their physical activity; even basic tasks, such as washing, dressing and eating, can become difficult. Treatment may include exercise programmes (pulmonary rehabilitation), and tablets designed to reduce processes in the lung which lead to scarring (antifibrotics). Increasing breathlessness can happen as a result of low oxygen levels, especially when trying to be active; it can even occur when oxygen levels are normal. There has been very little research into how to treat low oxygen levels for those with idiopathic pulmonary fibrosis; so far, there is no evidence as to whether using oxygen just for walking (ambulatory oxygen treatment) is helpful. This study planned to assess whether or not ambulatory oxygen therapy helped people with idiopathic pulmonary fibrosis. To test this, we designed a randomised controlled trial for 260 idiopathic pulmonary fibrosis patients who were breathless when walking. We had difficulty finding centres and patients to participate; therefore, the trial stopped early, with only seven participants. These difficulties were affected by the impact of COVID-19 on conducting research across the country and unexpected financial issues relating to how treatment was delivered from different centres. However, interviews with people not participating in the study suggested the study would be unappealing to patients and healthcare professionals regardless of other factors. Analysis of data from 37 interviews (patients, clinicians and commissioners) concluded that ambulatory oxygen therapy was acceptable and widely (perhaps universally) available. Patients held strong views that it should be provided when required. We conclude that further trials of ambulatory oxygen therapy in idiopathic pulmonary fibrosis are not appropriate and that research in future should focus on improving support services and oxygen technologies.